Exosomal PD-L1 contributes to immunosuppression and is associated with anti-PD-1 response - Chen, Gang; Huang, Alexander C.; Zhang, Wei; Zhang, Gao; Wu, Min; Xu, Wei; Yu, Zili; Yang, Jiegang; Wang, Beike; Sun, Honghong; Xia, Houfu; Man, Qiwen; et al. (Nature (London), 2018)
Tumour cells evade immune surveillance by upregulating the surface expression of programmed death-ligand 1 (PD-L1), which interacts with programmed death-1 (PD-1) receptor on T cells to elicit the immune checkpoint response 1 , 2 . Anti-PD-1 antibodies have shown remarkable promise in treating tumours, including metastatic melanoma 2 – 4 . However, the patient response rate is low 4 , 5 . A better understanding of PD-L1-mediated immune evasion is needed to predict patient response and improve treatment efficacy. Here we report that metastatic melanomas release extracellular vesicles, mostly in the form of exosomes, that carry PD-L1 on their surface. Stimulation with interferon-γ (IFN-γ) increases the amount of PD-L1 on these vesicles, which suppresses the function of CD8 T cells and facilitates tumour growth. In patients with metastatic melanoma, the level of circulating exosomal PD-L1 positively correlates with that of IFN-γ, and varies during the course of anti-PD-1 therapy. The magnitudes of the increase in circulating exosomal PD-L1 during early stages of treatment, as an indicator of the adaptive response of the tumour cells to T cell reinvigoration, stratifies clinical responders from non-responders. Our study unveils a mechanism by which tumour cells systemically suppress the immune system, and provides a rationale for the application of exosomal PD-L1 as a predictor for anti-PD-1 therapy. Melanoma cells release programmed death-ligand 1 (PD-L1) on the surface of circulating exosomes, suggesting a mechanism by which tumours could evade the immunesystem, and the potential application of exosomal PD-L1 to monitor patient responses to checkpoint therapies.